Dietary intake, cost of foods and associated factors of women with gestational diabetes - Gaffoor-Farooqui, Shabira (Department of Human Biology, 2025)
Background: Gestational Diabetes Mellitus (GDM) prevalence has increased globally over the last 20 years and according to the International Diabetes Federation (IDF), GDM prevalence in South Africa from 2011 to 2021 has increased by 11%. A study conducted in Johannesburg in 2018, highlighted that 9.1% (174/1906) of pregnant women developed GDM. Furthermore, an alarming 40% of women in South Africa with a history of GDM develop Type 2 Diabetes Mellitus (T2DM) within five years following their index pregnancy. Medical Nutrition Therapy (MNT) is essential in the treatment of GDM in combination with physical activity, lifestyle and behaviour change and a need exists for appropriate counselling and education. In low socioeconomic areas, implementing healthy diets is challenging, with affordability and availability being assumed as key barriers, necessitating and understanding food choice determinants. Developing viable solutions to these issues is essential for effective MNT, highlighting the need for further research to overcome these challenges. This Master's dissertation had two aims, with aim 1 investigating the dietary intake and associated factors of women with GDM and aim 2 to investigate determinants of cost and availability of foods (listed in the FFQ) and additional foods (not listed on FFQ) consumed by participants at baseline from the IINDIAGO study and compare to healthy and affordable alternatives where applicable. Methods: A cross-sectional descriptive study was conducted on n=205 women with GDM utilizing data from the IINDIAGO study. The IINDIAGO study is a convergent parallel mixed methods study with the main component being a pragmatic, 2-arm individually randomised controlled trial, which was carried out at five major referral centres and up to 26 well-baby clinics in the Western Cape and Gauteng provinces of South Africa. For the purpose of the current study only the baseline data in Cape Town were analysed. Dietary information was collected with the use of Food Frequency Questionnaires (FFQ) and interviewed-administered questionnaires were used to collect sociodemographic, socioeconomic, health behaviours, food security, psychosocial factors, past behaviour change attempts, perceived behavioural control and perceived barriers information. The costs of FFQ items at various supermarkets in Cape Town and availability of foods in areas participants resided was determined. A detailed cost evaluation was completed, and affordable healthy food alternatives were identified, culminating in the development of a diet plan based on the SEMDSA (2017) guidelines. Data were captured on REDCAP and subsequently transferred to Microsoft Excell 365 (Version 2309). The Statistical Package for Social Science (SPSS) was then used to analyse frequencies and means. Results: The findings revealed that participants' diets were energy-dense (ED) with a mean carbohydrate (CHO) intake of 417.6 ± 209.4g/d (70.4% of TE) and an alarmingly high intake of added sugars of 185.9 ± 191.5g/d (31.7% of TE). Table sugar, amongst the top 20 foods, contributed to the highest total energy intake (43.7%) as well as the top food item contributing to total CHO intake (61.3%). The top 40 commonly consumed food items revealed that sugar and some ED foods and snacks (crisps, fried chips, sausages, fried chicken, sausages, fruit juices) were significantly more expensive per portion per eaters in comparison to sugar sweetened beverages (SSB) and dairy fruit juice mixes. High fibre breakfast cereal (26.2%), brown bread (23.7%), fruit (11.3%), white bread (11%) and fried chips (7.6%) were the top contributors to fibre intake amongst participants. A significant portion of participants reported not consuming various types of porridge, such as 61.5% did not eat oats, 54.6% abstained from maize and a notable 95.6% abstained from consuming sorghum over the past month. Grains most consumed were white rice by 91.7% of participants followed by white pasta by 88.3%, while only 13.7% ate brown rice and 5.4% ate wholewheat pasta over the past month. The mean number of times fast food were consumed over a two-week period was 2.47 with 65.8% of participants consuming take-outs during preceding 2 weeks. The majority of participants added fats when preparing dishes such as rice, samp and barley (42.9%), yellow vegetables (52.7%), other vegetables (47.3%), pasta (64.9%) and baked potato (53.7%). The fats commonly used were soft tub margarine (60.5%), mixed oil or 'fish' oil (57.1%) and sunflower oil (30.2%). The five most commonly consumed foods by participants were fruit, potatoes, yellow vegetables, white rice and pasta. Less than a quarter (18.5%) experienced food security that led to either running out of money for food or the necessity to cut meal sizes or skip meals altogether, with less than 10% going to bed hungry due to affordability issues. The majority of women (81.4%) reported not experiencing food insecurity. A large proportion (60.9%) reported the cost of healthy food as a significant barrier to healthy eating. While the majority of participants were responsible for food preparation, about 40% perceived that they lacked sufficient knowledge in preparing healthy foods. Supermarkets in the areas where most participants resided stocked refined and ED foods (white bread, white pasta, deli-fried chicken, processed meats, hard brick margarine, fried ('slap') chips, doughnuts, potato chips, chocolates, sweets, cookies, crackers and soft drinks. Conversely, brown rice, barley, wholewheat pasta and certain low fat fresh produce (low fat and fat-free milk) were unavailable at some supermarkets. Seven basic healthy foods (wholewheat bread, brown rice, wholewheat pasta, soft tub margarine, grilled chicken, bran flakes, 2% low fat milk) collectively were 8.2% more expensive than their unhealthy counterparts. Utilizing the SEMDSA (2017) guidelines, a comparison of a healthy and unhealthy two-day diet plan revealed a minimal cost variation, with the healthy plan being 6.7% less expensive. The study further included a 7-day 8400 kJ (2000 Kcal) eating plan as a guideline. Regarding mental health, 48.5% of participants had no depression, while 40.1% were mildly to moderately depressed. Most (74.4%) reported receiving substantial social support and scored high (57.3%) for general life satisfaction (GLS). Less than a quarter received minimal social support, especially practical and financial support (14.9%) and 5.8% scored low for GLS. Only 27.8% of participants tried to exercise more to be healthier. Conclusion: Women of low socioeconomic status in Cape Town with GDM largely failed to meet the macronutrient guidelines established by the SEMDSA (2017) and international standards. Their diets were high in refined carbohydrates, sugars and ED foods with some foods such as chocolates, potato chips, fried chicken, processed meats, pies and desserts/puddings being often more expensive per portion per eaters than healthier alternatives. Fibre intake was suboptimal with inadequate vegetable diversity. Despite awareness of the dietary impact on GDM management, adherence to healthy eating was hindered by several barriers, including limited knowledge of nutritious foods, insufficient time for meal preparation and the high cost of healthier options. Although many participants reported food security, this status was likely aided by reliance on social grants by over half of them, raising concerns about sustainability, given the potential temporary nature of this support. For those experiencing food insecurity raises challenges, highlighting vulnerability among those at risk of insufficient support. Furthermore, the prevalence of unhealthy local food options presented additional challenges in making healthy dietary choices. Physical activity (PA) was also low, potentially due to time constraints, and/or insufficient guidance from health care professionals (HCP). While nearly half of participants had no depression, a significant portion experienced mild to moderate depression. Despite this, the majority reported receiving sufficient social support which could play a protective role in managing their mental and emotional well-being. The high levels of GLS for more than half of participants could suggest that many women still maintained a positive outlook on life, possibly aided by social support. The results also highlight gaps in support and proactive health behaviours as a minority received less social support, and a large proportion exercised less which indicates a need for greater focus in promoting health management behaviours, which are crucial for the management of GDM. Although basic healthy foods had minimal price difference in comparison to unhealthy foods and despite the efforts to calculate healthy diets at minimal costs, limited income and monthly costs can significantly burden low-income households, making adherence challenging without governmental assistance and cost-effective strategies. It is worthwhile to note that women with GDM do not necessarily eat drastically differently from non-pregnant or pregnant women of similar socioeconomic status in South Africa. However, their nutritional needs are more acute, and the persistence of poor dietary intake despite existing interventions, highlights a gap in program specificity. This study reinforces the need for targeted interventions and support strategies to assist these women achieve optimal nutrition and well-being and a need exists for further research for improved outcomes not just at baseline, but postpartum and in the prevention of T2DM.